Improving the physicochemical properties of Brazilian onshore and offshore crude oils using the production of blends. (1st November 2015) - Tozzi, Fabrício C.; Sad, Cristina M.S.; Bassane, João F.P.; dos Santos, Francine D.; Silva, Mayara; Filgueiras, Paulo R.; Dias, Heloísa P.; Romão, Wanderson; de Castro, Eustaquio V.R.; Lacerda, Valdemar
Graphical abstract: Highlights: Four oils were used for the production of 68 blends. New physicochemical properties of the blends were compared to the original oils. Thirteen blends exhibited an improvement in the TAN, total S, pour point and API. Oil A behaved as a "diluent" providing better quality in the properties. Abstract: When preparing a blend, a "new" oil is formed with characteristics that are different when compared to the original matrix (oil or blend). Thus, it is important to evaluate the impact of this mixture on the new physicochemical properties produced. In this study, four oils were used for the production of 68 blends as follows: two offshore oils designated as A and B (American Petroleum Industry (API) degree = 26.4 and 18.3, respectively) and two onshore oils designated as C and D (API degree = 12.2 and 19.6, respectively). The majority of the blends were classified as heavy. The new values of the physicochemical properties of the blends, such as total acidity number (TAN), total sulphur (S), pour point, API degree and kinematic viscosity, were tested and compared to the original oils. Among the 68 blends produced, 13 exhibited an improvement in the TAN, total S, pour point and API values. Two blends (named B30 and B34) exhibited the best results for TAN, total S, kinematic viscosity and API degree. Therefore, it can be concluded that when light oils are not produced in large amounts, their mixture with heavy oils allows the formation of mixtures with characteristics of relatively lighter oils, thus optimising the production, processing and refinement steps.